Individual Readiness for Change in Public Sector Organizations: A Systematic Review - Dian Dwi Nur Rahmah; Windhu Sugiarto; Endro Puspo Wiroko; Hardiansyah Hardiansyah; Edoardo Tondang (Psikostudia : Jurnal Psikologi, 2026)
Organizational change has become an inevitable phenomenon in the public sector, driven by rapid technological advancement, administrative reform, and increasing public demands for efficient and transparent services, requiring not only structural adjustments but also strong individual readiness to ensure successful transformation. This study aims to examine individual readiness for organizational change in public sector organizations by focusing on psychological, organizational, and technological factors that influence such readiness. The research employs a systematic literature review method, analyzing peer-reviewed journal articles published between 2020–2026 in English, covering psychological dimensions such as self-efficacy, intrinsic motivation, and resilience; organizational aspects including leadership, culture, and support; and technological elements such as digital competence and literacy. The findings reveal that individual readiness is shaped by the interaction between internal and external factors, where psychological aspects like self-efficacy, perception of change, intrinsic motivation, coping capacity, and adaptability play a critical role, while supportive leadership, effective communication, adaptive organizational culture, and institutional support further strengthen readiness; moreover, the growing integration of digital technologies increases the demand for technical skills, cognitive preparedness, and behavioral acceptance. The study implies that comprehensive change management strategies are essential, emphasizing the strengthening of psychological factors, enhancement of organizational support systems, and development of technological competencies through continuous training, participatory communication, and the cultivation of an adaptive organizational culture to support effective and sustainable public sector transformation.Perubahan organisasi telah menjadi fenomena yang tidak terhindarkan di sektor publik, didorong oleh pesatnya perkembangan teknologi, reformasi administrasi, serta meningkatnya tuntutan masyarakat akan layanan yang efisien dan transparan, sehingga memerlukan tidak hanya penyesuaian struktural tetapi juga kesiapan individu yang kuat untuk memastikan keberhasilan proses transformasi. Penelitian ini bertujuan untuk mengkaji kesiapan individu dalam menghadapi perubahan organisasi di sektor publik dengan menitikberatkan pada faktor psikologis, organisasional, dan teknologi yang memengaruhinya. Penelitian ini menggunakan metode systematic literature review dengan menganalisis artikel jurnal terindeks yang diterbitkan pada tahun 2020–2026 dalam bahasa Inggris, yang mencakup dimensi psikologis seperti self-efficacy, motivasi intrinsik, dan resiliensi; aspek organisasional seperti kepemimpinan, budaya, dan dukungan; serta elemen teknologi seperti kompetensi dan literasi digital. Hasil penelitian menunjukkan bahwa kesiapan individu dibentuk oleh interaksi antara faktor internal dan eksternal, di mana aspek psikologis seperti self-efficacy, persepsi terhadap perubahan, motivasi intrinsik, kapasitas coping, dan kemampuan adaptasi memegang peran penting, sementara kepemimpinan yang suportif, komunikasi yang efektif, budaya organisasi yang adaptif, serta dukungan institusional semakin memperkuat kesiapan tersebut; selain itu, meningkatnya integrasi teknologi digital juga memperbesar tuntutan terhadap keterampilan teknis, kesiapan kognitif, dan penerimaan perilaku individu. Penelitian ini mengimplikasikan pentingnya strategi manajemen perubahan yang komprehensif, dengan menekankan penguatan faktor psikologis, peningkatan sistem dukungan organisasi, serta pengembangan kompetensi teknologi melalui pelatihan berkelanjutan, komunikasi partisipatif, dan pembentukan budaya organisasi yang adaptif guna mendukung transformasi sektor publik yang efektif dan berkelanjutan.